2011
DOI: 10.1016/j.ejso.2011.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The value of post-neoadjuvant therapy PET-CT in the detection of interval metastases in esophageal carcinoma

Abstract: Background PET-CT scanning is increasingly applied in the primary work-up of esophageal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 18 publications
8
29
0
Order By: Relevance
“…First, we shown that pre-RT/CCRT PET results may prompt treatment modification in as many as 24 % of highrisk OSCC patients. Recently, Blom et al showed the potential value of an additional PET scan in high-risk cancer patients before the initiation of curative treatment [18]. These authors performed an additional PET scan in oesophageal cancer patients during post-neoadjuvant therapy and before surgery to detect the presence of interval metastases.…”
Section: Discussionmentioning
confidence: 96%
“…First, we shown that pre-RT/CCRT PET results may prompt treatment modification in as many as 24 % of highrisk OSCC patients. Recently, Blom et al showed the potential value of an additional PET scan in high-risk cancer patients before the initiation of curative treatment [18]. These authors performed an additional PET scan in oesophageal cancer patients during post-neoadjuvant therapy and before surgery to detect the presence of interval metastases.…”
Section: Discussionmentioning
confidence: 96%
“…Interval metastases may be detected in the liver, lungs, distant lymph nodes, and bone. 46,47 The presence of distant metastases at unusual sites, such as skeletal muscle, has also been reported. 46 Because the presence of distant metastases dramatically changes the treatment plan and some of them may be outside the visual range of routine stand-alone CT imaging, 18 F-FDG PET/CT is a preferred imaging modality of choice in this setting.…”
Section: Restagingmentioning
confidence: 96%
“…However, the number of false-positive 18 F-FDG PET/CT results for distant metastases seems to be low. 47,48 A common cause for false-positive results is inflammation or infection. False-positive results have been encountered in up to 8% of the patients.…”
Section: Restagingmentioning
confidence: 99%
See 1 more Smart Citation
“…PET-CT can be used, however, to detect interval metastases [42]. Radiation causes an inflammatory reaction of the oesophagus and its surrounding tissue, thus inducing FDG-uptake with a false positive interpretation.…”
Section: Characteristicmentioning
confidence: 97%